Electronic cigarettes and obstetric outcomes: a prospective observational study. (9th February 2020) - McDonnell, BP; Dicker, P; Regan, CL
Abstract : Objective: To compare the obstetric outcomes and socio‐demographic factors in electronic cigarette (EC) users with cigarette smokers and non‐smokers in pregnancy. Design: Prospective observational cohort study. Setting: A large urban maternity hospital delivering almost 8500 infants per year. Population: Pregnant women attending for antenatal care. Methods: Electronic cigarette users at time of booking history were prospectively identified. Maternal and neonatal outcomes were compared with those of pregnant smokers and non‐smokers. Multiple logistic regression analysis was performed to estimate the association between the explanatory variables and birthweight. Main outcomes measures: Infant birthweight, gestation at delivery, incidence of low birthweight. Results: A total of 218 women with exclusive EC use and 195 women with dual use of both cigarettes and EC, had a live birth during the study period. EC users were of higher socio‐economic status than smokers. Infants born to EC users had a mean birthweight of 3470 g (± 555 g), which was similar to that of non‐smokers (3471 ± 504 g, P = 0.97) and significantly greater than that of smokers (3166 ± 502 g, P < 0.001). The mean birth centile of EC users was similar to non‐smokers (51st centile versus 47th centile, P = 0.28) and significantly greater than that of smokers (27th centile, P < 0.001). Dual users had a mean birthweight and birth centile similar to that of smokers. Conclusion: The birthweight of infants born to EC users is similar to that of non‐smokers, and significantly greater than cigarette smokers. Dual users of both cigarettes and EC have a birthweight similar to that of smokers. Tweetable extract: Birthweight of infants born to electronic cigarette users appears to be similar to that of non‐smokers. Tweetable extract: Birthweight of infants born to electronic cigarette users appears to be similar to that of non‐smokers.